Cell-Based Vital Organs Specific Biomarkers Assessment using Biofield Energy Based Novel Test Formulation - Janice Patricia Kinney; Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Gopal Nayak; Mayank Gangwar; Snehasis Jana (Journal of Biotechnology and Biomedical Science, 2019)
The aim of the present study was to determine the impact of Biofield Energy Treated test formulation using six differentcell-lines. The test formulation/item (TI) and cell media (Med) was divided into two parts; one part was untreated (UT) and other part received Biofield Energy Treatment remotely by a renowned Biofield Energy Healer, Janice Patricia Kinney, USA and labeled as Biofield Energy Treated (BT) test item (TI)/media. Based on cell viability assay, test formulation was found as safe at tested concentrations. Cytoprotective activity of test formulation showed a significant restoration of cell viability by 60.6% (10 µg/mL), 67.5% (63.75 µg/mL), and 117.5% (63.75 µg/mL) in UT-Med + BT-TI, BT-Med + UT-TI, BT-Med + BT-TI, respectively compared to untreated in human cardiac fibroblasts cells (HCF) cells. Moreover, restoration of cell viability was improved by 64% and 127.3% in UT-Med + BT-TI and BT-Med + UT-TI, respectively at 1 µg/mL compared to untreated in human liver cancer (HepG2) cells. Cellular restoration in A549 cells was improved by 314% and 112.3% at 1 µg/mL in BT-Med + UT-TI and BT-Med + BT-TI, respectively than untreated. ALP activity in Ishikawa cells was significantly increased by 175.5%, 547.2%, and 220.8% in UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI, respectively at 0.1 µg/mL as compared to untreated. Additionally, in MG-63 cells showed increased ALP activity by 76.9%, 78.4%, and 79% in UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI, respectively at 50 µg/mL compared to untreated. The percent cellular protection of HCF (heart) cells (decreased of LDH activity) was significantly increased by 60.6% (10 µg/mL), 67.5% (63.75 µg/mL), and 117.5% (63.75 µg/mL) in UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI, respectively as compared to untreated. An improved HepG2 cells protection (represents decreased ALT activity) by 115.1% (1 µg/mL), 42.5% (25.5 µg/mL), and 60.8% (10 µg/mL) in UT-Med + BT-TI, BT-Med + UT-TI, BT-Med + BT-TI, respectively as compared to untreated. Percentage cellular protection of A549 (lungs) cells (represents increased of SOD activity) was significantly increased by 191.1% and 81.4% at 0.1 µg/mL in UT-Med + BT-TI and BT-Med + BT-TI, respectively as compared to untreated. Serotonin level was significantly increased by 31.8% (10 µg/mL) and 56.9% (25.5 µg/mL) in UT-Med + BT-TI and BT-Med + BT-TI, respectively compared to untreated in human neuroblastoma cells (SH-SY5Y). Relative quantification (RQ) of vitamin D receptor (VDR) was significantly increased by 304.3% (0.01 µg/mL), 128.4% (0.1 µg/mL), and 240% (0.1 µg/mL) in UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI, respectively compared to untreated in MG-63 cells. Thus, Biofield Energy Treated test formulation (The Trivedi Effect®) significantly improved organ specific functional biomarkers and would be useful for multiple organs health related to coronary artery disease, arrhythmias, congenital heart disease, cardiomyopathy, cirrhosis, liver cancer, hemochromatosis, asthma, chronic bronchitis, cystic fibrosis, osteoporosis, etc.
Keywords: Biofield Energy Treatment